EVALUASI PROGRAM PENDIDIKAN GURU MIPA UNGGULAN (PGMIPAU) BERDASARKAN MODEL CIPP (Context, Input, Process, Product) PADA MAHASISWA PRODI PENDIDIKAN KIMIA - Nur A. Limatahu; Khusna A. Rakhman; Muhammad Hidayat J.M; Indra Cipta (Pascasarjana Universitas Negeri Medan, 2014)
Abstract It has been researched the evaluation of PGMIPAU program based on the Context, Input, Process, Product (CIPP) model to chemistry education department, PGMIPAU classes, 2013/2014. The goal of the research was to evaluate the PGMIPAU program by using CIPP model and to analyse each aspect of it in order to give decision and recommendation about the program continuation. To achieve the goal of the research, we conducted the qualitative descriptive research. The samples were the management of chemistry education department, the faculties of PGMIPAU subjects which consisted of analytical chemistry II, english for chemistry II, and physical chemistry II at PGMIPAU classes, and the students of PGMIPAU. The data were acquired by interview, queisioner, and academic test. The data avaluation were done by using triangulation data and queisioner analysis was used descriptive statistic, scale 5. The result of the research showed that several aspects which corroded the PGMIPA program from CIPP model point of view. As general, there were minor factors which affected the lerning outcome, however it might be fixed in the future for perfection of this program. Based on the evaluation result to PGMIPAU program using CIPP model, it was decided that PGMIPAU program should be continued and needed several notes to has it perfected.